If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25(12x + 16) = 10 + -3(x + -2) Reorder the terms: 0.25(16 + 12x) = 10 + -3(x + -2) (16 * 0.25 + 12x * 0.25) = 10 + -3(x + -2) (4 + 3x) = 10 + -3(x + -2) Reorder the terms: 4 + 3x = 10 + -3(-2 + x) 4 + 3x = 10 + (-2 * -3 + x * -3) 4 + 3x = 10 + (6 + -3x) Combine like terms: 10 + 6 = 16 4 + 3x = 16 + -3x Solving 4 + 3x = 16 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4 + 3x + 3x = 16 + -3x + 3x Combine like terms: 3x + 3x = 6x 4 + 6x = 16 + -3x + 3x Combine like terms: -3x + 3x = 0 4 + 6x = 16 + 0 4 + 6x = 16 Add '-4' to each side of the equation. 4 + -4 + 6x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 16 + -4 6x = 16 + -4 Combine like terms: 16 + -4 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| x-9x+3+8x-3= | | -6(n+4)+25=-2n-11 | | 8x+9=8x+6 | | 12(n-4)-3n= | | 5n-3=-43 | | -6x+6+7x=-13+5 | | 9=-2k+27 | | -7(w-4)+3w-27= | | 4=y-5 | | 2x^2=2x+3 | | 3x-(x-4)=2x | | 2(v-5)+7v+4= | | -4(5q+5)+4(q-4)= | | 3(4-c)-22=17c-5(2+4c) | | 6x^2+40x-14=0 | | 5w+3(9-2w)=18 | | 5(6x+8+-2x)=-10 | | -3x-2(2x+27)=-124 | | 12a+3+18-9a= | | 5x+6=2x-4 | | -5+5a-4-2a+3a= | | 3b-3-11b-9= | | 1x+6=2x-4 | | -7+g+1-6g= | | x+4*7=70 | | 18(x-2)-4(-9+3x)=-14 | | 5z-4=3(z+2) | | x-16=44 | | 3A-4=-13 | | 9x+8=3x-7 | | x^3+3x^2=18x | | -18(c-1)-18= |